Kinerja Pengawas Lembaga Perkreditan Desa dan Faktor yang Mempengaruhinya Dimoderasi Budaya Tri Hita Karana - Eka Damayanthi, I Gst Ayu; Lely Aryani Merkusiwati, Ni K. (E-Jurnal Akuntansi; Vol 31 No 4 (2021), 2021)
This research was conducted by considering the inconsistency of research results regarding the influence of independence, professionalism and accounting information systems on the performance of the Supervisory Body as the internal controller of the LPD by moderating the organizational culture of Tri Hita Karana. The sample in this study amounted to 35 LPDs in Denpasar City. The data collection method used was a questionnaire. The data analysis technique used in testing the hypothesis of this study is multiple linear regression. The results of this study are that independence has a positive effect on the performance of LPD supervisors, professionalism and SIA have no effect on supervisor performance, the Tri Hita Karana culture is able to moderate and strengthen the influence of independence. on LPD staffing performance, and tri-black culture because it has not been able to moderate the influence of professionalism and BSM on the performance of LPD supervisors in Denpasar City. Keywords: LPD Supervisory Body Performance; Independence; Professionalism; SIA; Tri Hita Karana Culture.